The History of Mycoplasma pneumoniae Pneumonia - Saraya, Takeshi (Frontiers in Microbiology, 2016)
In the United States in the 1930s, although the pathogen was not known, atypical pneumonia was clinically distinguished from pneumococcal pneumonia by its resistance to sulfonamides. Reimann (1938) reported seven patients with an unusual form of tracheo bronchopneumonia and severe constitutional symptoms. He believed the clinical picture of this disease differed from that of the disease caused by influenza viruses or known bacteria and instead suspected “primary atypical pneumonia.” For many years, the responsible infectious agent was tentatively classified as a filterable virus that could pass through a Seitz filter to remove bacteria and was reported to be a psittacosis-like or new virus. After that, Eaton et al. (1942, 1944, 1945) identified an agent that was the principal cause of primary atypical pneumonia using cotton rats, hamsters, and chick embryos. Eaton et al. (1942, 1944, 1945) did not perform an inoculation study in human volunteers. During the 1940s, there were three groups engaged in discovering the etiology of the primary atypical pneumonia. (1) Commission on Acute Respiratory Diseases Diseases directed by John Dingle, (2) Dr. Monroe Eaton’s group, the Virus Research Laboratory of the California State Public Health Department, (3) The Hospital of the Rockefeller Institute for Medical Research directed by Horsfall. During 1940s, the members of the Commission on Acute Respiratory Diseases concluded that the bacteria-free filtrates obtained from the patients, presumably containing a virus, could induce primary atypical pneumonia in human volunteers via Pinehurst trials. During 1950s, serological approaches for identification of the Eaton agent developed such as Fluorescent-Stainable Antibody, and at the beginning of the1960s, the Eaton agent successfully grew in media, and finally accepted as a cause of primary atypical pneumonia. Thus, technical difficulties with visualizing the agent and failure to recognize the full significance of the Pinehurst transmission experiments resulted in a lapse of 20 years before acceptance of the Eaton agent as Mycoplasma pneumoniae. This review describes the history of M. pneumoniae pneumonia with a special focus on the recognition between the 1930 and 1960s of the Eaton agent as the infectious cause.